2014
DOI: 10.1016/j.jtcvs.2014.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve surgery: Right lateral minithoracotomy or sternotomy? A systematic review and meta-analysis

Abstract: MIVS and conventional mitral valve surgery have a similar perioperative outcome. Mitral valve surgery via a right lateral minithoracotomy seems to be favorable with regard to resource-related outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(44 citation statements)
references
References 43 publications
4
40
0
Order By: Relevance
“…A recent meta-analysis confirms these findings with a significant improvement in freedom from reoperation of MIMVS at eight years. 16,17 The application of the ''respect'' instead of ''resect'' technique by using premanufactured Gore-Tex loops with pledgets in 68.8% of our patients might explain the high durability of repair and little need for reoperation in the long-term. 19 Short-term outcome results did not show a significant difference between the resection versus loop technique, 12,26 but the longer coaptation line that can be achieved may result in superior durability.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A recent meta-analysis confirms these findings with a significant improvement in freedom from reoperation of MIMVS at eight years. 16,17 The application of the ''respect'' instead of ''resect'' technique by using premanufactured Gore-Tex loops with pledgets in 68.8% of our patients might explain the high durability of repair and little need for reoperation in the long-term. 19 Short-term outcome results did not show a significant difference between the resection versus loop technique, 12,26 but the longer coaptation line that can be achieved may result in superior durability.…”
Section: Discussionmentioning
confidence: 89%
“…10,13,14,24 A more recent metaanalysis was unable to show a higher stroke rate with MIMVS. 17 Advanced age, retrograde perfusion, 13 and endoartic clamping 16 were identified as risk factors. Thirty percent of our patients were older than 75 without any impact of the outcome which is in line with the finding of Holzhey et al that MIMVS is a safe approach for elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth intercostal incision along the lower edge of the right breast is sufficient to expose the operative field without rib excision. This incision, which is located in the skin folds below the breast, does not affect the cosmetic appearance, is especially suitable for female patients, and can greatly reduce the psychological shadow and psychological barriers caused by postoperative scarring [ 17 , 18 ]. The length of the thoracic incision in complete thoracoscopic surgery equals the minimally required length that allows the prosthetic valve into the thoracic cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have consistently shown that MIMVS was associated with equivalent mortality and major morbidity compared with conventional surgery but with superior cosmesis, faster recovery and return to baseline function, as well as lower risk of atrial fibrillation, bleeding, and transfusion, reduced ICU and ventilation times, and reduced hospital costs [24][25][26]. A US Hospital database propensity matching study from 2007 to 2011 for mitral repair hospitalizations in more than 600 hospitals showed that MIMVS was associated with similar mortality, less morbidity, fewer infections, shorter stay and less readmission, and significant cost savings during primary admission [25].…”
Section: Minimally Invasive Approachesmentioning
confidence: 99%